2022
DOI: 10.3390/mi13030365
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Lateral Displacement Microfluidic Chip for Minicell Purification

Abstract: Deterministic lateral displacement (DLD) is a well-known microfluidic technique for particle separation with high potential for integration into bioreactors for therapeutic applications. Separation is based on the interaction of suspended particles in a liquid flowing through an array of microposts under low Reynolds conditions. This technique has been used previously to separate living cells of different sizes but similar shapes. Here, we present a DLD microchip to separate rod-shaped bacterial cells up to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…DLD is a useful tool for the continuous separation of micrometer-sized particles such as bacteria, parasites, and tumor cells in the blood. [46,47] In general, this process utilizes laminar flow through a periodic array of obstacles (e.g., pillars) in a microfluidic device (see Figure 4), where the total fluid flux between each gap of the obstacles is divided into multiple streamlines. [46] Each streamline contains an equal fluid flux.…”
Section: Deterministic Lateral Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…DLD is a useful tool for the continuous separation of micrometer-sized particles such as bacteria, parasites, and tumor cells in the blood. [46,47] In general, this process utilizes laminar flow through a periodic array of obstacles (e.g., pillars) in a microfluidic device (see Figure 4), where the total fluid flux between each gap of the obstacles is divided into multiple streamlines. [46] Each streamline contains an equal fluid flux.…”
Section: Deterministic Lateral Displacementmentioning
confidence: 99%
“…[46,49] Recently, our groups reported the separation of cells with rodlike and spherical morphologies with high efficiency of 75.5% by inserting a mixed solution containing both cell types into a DLD chip and using a flow rate of 50 μL min −1 . [47] Within the present work, we manufactured DLD chips with a row shift angle of 1°a nd a D c of 800 nm and 1.4 μm, respectively. Using Equation (S4) (Supporting Information) we calculated a pillar spacing G of 4 μm for a D c of 800 nm and of 7 μm for a D c of 1.4 μm.…”
Section: Deterministic Lateral Displacementmentioning
confidence: 99%
“…25 Most importantly, they can separate cells without the need for sample pretreatment, such as labeling or lysis. 26 These advantages have made DLD a widely used method for separating and enriching samples containing various cell types and biological particles, including stem cells, 27 circulating tumor cells (CTCs), 28,29 blood cells, 30,31 bacteria, 32 bacterial minicells, 33 parasites, 34 spores, 35 and nano-sized particles. 36 Despite these benefits, several limitations of DLD devices have been identified such as low-throughput (ranging from 1 nL min −1 to 10 μL min −1 ), 22 occlusion in the regions around the posts, suboptimal purity of cell recovery (<70%), 25 and the requirement for hydrodynamic sample focusing using a sheath flow (see Table S1…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Deterministic lateral displacement (DLD) is a well-known passive hydrodynamic separation method that relies on an array of micropillars to alter the path of particles based on their size and deformability. 37 Nearly all prior DLD works have used syringe pumps [38][39][40][41][42][44][45][46][47] or pressure regulators 43,[48][49][50][51][52][53][54][55][56][57][58][59] which increase the cost of using DLD and reduce the likelihood of its use in resource-limited situations. Few studies have accomplished a passive fluid driving method, 60,62,63 but in each of these cases, the separated products flow directly into the pump with no opportunity for direct product collection, though Tran et al 61 showed that cells drawn into the paper wick can be eluted after separation and are still viable.…”
Section: Introductionmentioning
confidence: 99%